P96 Physiotherapy management of adult patients with cystic fibrosis on Intensive Care Units (ICU) – a survey of uk physiotherapists. (15th November 2016) - Cathcart, F; Parrott, H; Jones, A; Simmonds, N
Abstract : Introduction and objectives: Currently no guidelines or data exist on the physiotherapy management of adults with CF on the ICU. The aim was to explore the views and experiences of the specialist physiotherapists (SPs) managing adults with CF admitted to an ICU. Methods: An online survey was designed which included questions (open and closed) on staff confidence, communication, learning needs, extracorporeal membrane oxygenation (ECMO) and end of life care. The survey was sent to CF, ICU and transplant SPs across the UK. Results: 42 SPs responded (74% response rate), 52% (n = 22) adult CF, 40% (n = 17) ICU and 7% (n = 3) transplant specialists. 73% (n = 30) had been specialists in their area for >5 years. 27% (n = 11) reported no CF admissions to their ICU in the last year, only 24% (n = 10) had >3 in the last year. Physiotherapy care was shared between the ICU and CF SPs teams in 43% (n = 18) of respondents. 90% (n = 37) felt this joint working was essential to optimise patient care. On a confidence scale of 1 – 10 (1 = low, 10 = high) the median (IQR) confidence score of SPs to manage patients with CF on ICU was 7 (7–9). 43% (n = 17) had experienced pre transplant patients with CF being invasively ventilated and reported that the challenges included airway clearance, weaning, inhalation therapy and nursing staff education. Of the 17 respondents who worked in ECMO centres, 57% (n = 12) had never had a patient with CF on ECMO and 90% had no physiotherapy ECMO protocol. Reported challenges were mobilisation, chest clearance, inhalation therapy and palliative care. Of respondents 50% (n = 21) had managed a patient with CF who died on ICU. 79% (n = 33) of respondents wanted more education on managing patients with CF on ICU with comments around, joint training, national guidelines being developed and the importance of collaborative care. Conclusions: The number of adults with CF admitted to ICU remains low nationally however SPs need to maintain competence and confidence in managing these complex patients. National, expert consensus guideline development, including a physiotherapy ECMO protocol would assist in ensuring equitable quality care in this setting.